SOCIETY’S EMPOWERMENT THROUGH THE UTILIZATION OF PRODUCTIVE ZAKAT AT DOMPET DHUAFA AMIL ZAKAT INSTITUTION OF SOUTH SULAWESI - M. Nasir Hamzah; Muslimin H. Kara; Amiruddin K.; Raehana, Syarifa (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The main problem of this research is how to empower society through utilizing productive zakat at the Dompet Dhuafa Amil Zakat institution of South Sulawesi. This study classifies the main issue into three problems: (1) What is productive zakat utilization in the Dompet Dhuafa Amil Zakat institution of South Sulawesi? (2) What factors influence society empowerment through utilizing productive zakat in Dompet Dhuafa Amil Zakat institution of South Sulawesi? And (3) The impact of the utilization of productive zakat at Dompet Dhuafa Amil Zakat institution of South Sulawesi on Society Empowerment. The approach used in this study was qualitative descriptive in terms of Case study. The results of this study were; First, the form of productive zakat utilization carried out by Dompet Dhuafa Amil Zakat institution of South Sulawesi, namely 1). Surplus Zakat Budget; refers to Amil’s zakat funds as companies’ funding by making mustahik zakat as workers. 2) In-Kind; refers to zakat funds given in the form of production tools used by mustahik to run a productive business. 3). Revolving Fund; it refers to the utilization of zakat by providing loan funds to mustahik in the form of qardhul hasan or benevolent loans.